How Do Different Growth Forms of Winter Submerged Macrophytes Species Respond to Underwater Light Quality in a Mesocosm Study? - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Chenxin Zhong; Zian Xiang; Ye Yao; Lishuai Zhang; Sizhuo Li (Ecology and Evolution)
ABSTRACT Underwater light is a key factor that affects the growth of submerged macrophytes. However, the responses of different growth forms of submerged macrophytes to light quality remain unclear. The morphological, physiological, photosynthetic, and stoichiometric responses of erect Potamogeton crispus (P. crispus) and low‐canopy Elodea nuttallii (E. nuttallii) to six different light qualities (white light, R/B = 1:8, 1: 4, 1:1, 4:1, 8:1) were studied by a control experiment. (1) No significant differences were observed in the germination number, leaf length, and leaf width of P. crispus under different light qualities (p > 0.05). Both P. crispus and E. nuttallii produced greater plant heights, more leaves and branches under more red light (4:1, 8:1), which was beneficial for the extension of leaves. Under white light, the germination number of P. crispus, adventitious roots of E. nuttallii, and branch number of P. crispus and E. nuttallii were the lowest. (2) Compared to red light, more blue light (1:4, 1:8) was more conducive to the synthesis of photosynthetic pigments. However, excessive blue and red light was not conducive to the accumulation of pigments. The result of malondialdehyde showed that the physiological stress induced by blue light in P. crispus and E. nuttallii was stronger. (3) The N:P, C:N, and C:P ratios of P. crispus and E. nuttallii were higher under more red light, which was beneficial for the synthesis of nutrients in two submerged macrophy; however, the contents of TN and TP in E. nuttallii were higher under more blue light. Two different growth forms of submerged macrophytes grew better under red light, and better adapted to the eutrophic water dominated by red light. However, for aquatic restoration, other submerged macrophytes need to be supplemented after the water quality is improved.